Sunscreen Cream Formulation of Noni Leaf Extract (Morinda citrifolia L.) with Emulsifier Combination of Tween 80 and Lecithin - Bianca Levie Tania; Rini Dwiastuti; Agatha Budi Susiana Lestari; Dewi Setyaningsih (Universitas Airlangga, 2022)
Background: Noni leaf (Morinda citrifolia L.) extract is a natural product that can be used as a sunscreen. The extract contains flavonoids which function act as an antioxidant. In this work, sunscreen cream formulated with noni leaf extract was prepared using a combination of tween 80 and lecithin. Objective: The purpose of this study is to evaluate how the combination of tween 80 and lecithin affects the physical qualities of the cream, such as organoleptic, homogeneity, emulsion type, spreadability, adhesion, pH, and stability over 28 days of storage at room temperature, and to find the best formula. Methods: This study used 10% of noni leaf extract in the cream formulation. The Simplex Lattice Design (SLD) method was used to determine the effect of different concentrations of the two emulsifiers on the cream's spreadability, adhesion, and pH. Furthermore, the SLD was used to find the best formula. Results: The results showed that different concentrations of the emulsifier, which are the tween 80 and lecithin combination, affected the physical properties and storage stability of cream preparations. The interaction of tween 80 and lecithin is having a significant impact on the cream's adhesion and spreadability; however, the effect of the interaction on the pH value was not significant. Conclusion: The formula containing 2.5 % tween 80 and 2.5 percent lecithin was found to be the most effective in fulfilling the cream physical properties while remaining stable during storage.